Cholelithiasis-diagnostic approach: are clinical presentations in children different? - Rajoo, Theyveeka Selvy; Naidu, Janakan; Naidu, Senevahsan; Ramli, Julian M.; Khairy, Azuddin M. (International Surgery Journal, 2022)
Cholecystitis has been considered an uncommon entity in children, but it’s incidence is reportedly increasing which may be attributed to widespread use of diagnostic imaging (ultrasonography). A healthy 11-year-old female Indian child presented to the emergency department with a chief complaint of abdominal pain. The pain was at the epigastric region and accompanied with vomiting. As per the complete examination and findings, a diagnosis of constipation colic was made. A month later, the patient presented with the same chief complaint, but general physical examination revealed tenderness at the right hypochondrium, and Murphy’s sign was positive. Upon performing an abdominal ultrasound, multiple small gallstones were noted in an otherwise normal gallbladder. No biliary obstruction was seen. A diagnosis of acute cholecystitis was made. Patient was then admitted and treated with a course of antibiotics. The incidence of cholelithiasis in children has not been sufficiently studied. The incidence of cholecystitis in India was found to be 0.3% with the incidence in age group 0-10 being less than 0.1%. In contrast to adult cholecystitis, it has been found that there is female predominance of cholecystitis in children. In children, 20% to 50% gallstones are radiopaque. Unknown causes are still prevalent in stone formation. Hence, the purpose of this paper was to increase awareness about the diagnosis of cholelithiasis in children. The probability of cholecystitis in children should not be ignored. Cholelithiasis should always be considered as a differential diagnosis when children present with complaints of abdominal pain.